Evaluation the Efficacy of HBA Sperm- Hyaluronan Binding Assay Method in Infertility Centers - Forouzan Absalan; Sirous Rostami; Abdollah Zabihi (Negah Institute for Scientific Communication, 2014)
Introduction: The novel development of the (HBA) sperm- hyaluronan binding assay has now been routinely used in some laboratories worldwide to predict sperm maturity and functionality. The purpose of this study was to evaluate the correlation between HBA score and histone deficiency, protamine content and DNA fragmentation. Methods: During April- March 2012 patients who were enrolled at Shiraz- Human Assisted Reproductive Center were included in this study. Semen sample from 100 men were assessed during this study. Patients were divided into two groups, group A (%15≤HBA≤%55) n = 50 and group B (HBA≥ %55) n = 50. Sperm analysis carried out according to World Health Organization criteria. Histon efficiency, protamine content, and DNA integrity were assessed by Aniline blue, Chromomycine A3 staining and sperm chromatin dispersion test. Results: The results show positive correlation between sperm concentration and motility with percentage HA-bounded sperms while a negative correlation with percentage abnormal morphology. Histone deficiency assessed using Aniline blue staining show significant difference in group A 18.22±1.06 compared with group B 32.43± 2.90. Furthermore, the percentage HAbounded sperm showed a significant negative correlation with protamine deficiency assessed by CMA3 staining spermatozoa (15.06± 0.88 in group A versus. 75.17± 2.37 in group B). The results also show a positive correlation between intact DNA with HA bound ability. Conclusion: The results indicating that HBA had a high degree of selectivity for sperm with histone efficiency, protamine quality, and high DNA integrity. These findings are important from the points of view of human sperm DNA integrity, sperm function, and the potential efficacy of HA-mediated sperm selection for human assisted reproduction techniques.